Creating culture, performing community: an Angahuan wedding story - Martinez-Rivera, Mintzi Auanda (Underground cultures, 2025)
"Creating Culture, Performing Community explores the ways in which the people of Santo Santiago de Angahuan, a P'urhépecha community in the state of Michoacán, México, create and curate their cultural practices and how, by doing so, they perform what it means to be an active member of the P'urhépecha community. Through a deep ethnographic account of ritual practices, author Mintzi Auanda Martínez-Rivera focuses on the tembuchakua, or wedding rituals, analyzing their creation, performance, and transformation within the P'urhépecha community. By proposing alternative approaches to understanding indigeneity, Martínez-Rivera showcases how people carefully transform their cultural practices and rearticulate and perform their identities. Thus Creating Culture, Performing Community has three main aims: to analyze how people create their own culture; to showcase how cultural practices are performed to reflect particular ideas of what it means to be a member of a community; and to move beyond limited understandings of indigenous identity and cultural practices"-- Provided by publisher